2002
DOI: 10.1161/01.cir.0000029802.88087.5e
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Fulfilling Prophecy

Abstract: Background-Given the central importance of nitric oxide (NO) in the development and clinical course of cardiovascular diseases, we sought to determine whether the powerful predictive value of C-reactive protein (CRP) might be explained through an effect on NO production. Methods and Results-Endothelial cells (ECs) were incubated with recombinant CRP (0 to 100 g/mL, 24 hours), and NO and cyclic guanosine monophosphate (cGMP) production was assessed. The effects of CRP on endothelial NO synthase (eNOS) protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
324
4
10

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 903 publications
(351 citation statements)
references
References 43 publications
13
324
4
10
Order By: Relevance
“…Several other inflammatory markers for prediction of coronary accidents in healthy men and women and in patients with stable angina, acute coronary diseases and in follow up of cardiovascular accident have been studied. These markers include Values are mean ± SD; P [ 0.05 not significant; P \ 0.0001 highly significant interleukin (IL-6) [20,21], serum amyloid A (SAA) [22], Tumour necrosis factor-a (TNF-a) [23], CD40 ligand [24]. Among these markers CRP has emerged as most powerful inflammatory marker of future cardiovascular risk [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Several other inflammatory markers for prediction of coronary accidents in healthy men and women and in patients with stable angina, acute coronary diseases and in follow up of cardiovascular accident have been studied. These markers include Values are mean ± SD; P [ 0.05 not significant; P \ 0.0001 highly significant interleukin (IL-6) [20,21], serum amyloid A (SAA) [22], Tumour necrosis factor-a (TNF-a) [23], CD40 ligand [24]. Among these markers CRP has emerged as most powerful inflammatory marker of future cardiovascular risk [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, as most of the experiments were in tissue culture with cause-effect exhibited following the use of commercial CRP preparations concern has been raised for spurious effects of contaminants. When impurities, in particular the preservative sodium azide and the contaminant endotoxin, are removed from commercial CRP preparations the putative direct endothelial activity is questioned [23][24][25][26][27][28]. Transgenic animals that express human CRP, or mice that express rabbit CRP [20], can be used to resolve the issue of this suspected spurious artifactual results.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies, both in the injured artery and the distant lung tissue, indicate that CRP exerts an opposite effect, with suppression of p38 MAPK. These contradictory findings may result from the in vitro methodology which exposes the study to the risk of contamination with preservatives and endotoxin [23][24][25][26][27][28]. Another explanation is a possible differential effect of CRP on blood mononuclear cells and arterial and alveolar cells.…”
Section: Discussionmentioning
confidence: 99%
“…In cell culture, proinflammatory factors such as TNF-α, CRP, and ox-LDL downregulate expression of endothelial nitric oxide synthase (eNOS) and thus decrease nitric oxide production (Vallance et al 1997, Verma et al 2002. This effect appears to be mediated via a decrease in the stability of eNOS messenger RNA (Verma et al 2002). Whereas it is clear that cytokines such as TNF-α activate endothelial cells, recent studies have raised the possibility that the reported effects of the acute phase reactant CRP might be attributable to contaminants in commercially available preparations.…”
Section: Experimental Studies Of Endothelial Activation By Proinflammmentioning
confidence: 99%
“…An important consequence of endothelial activation is a decrease in the bioavailability of endothelium-derived nitric oxide. In cell culture, proinflammatory factors such as TNF-α, CRP, and ox-LDL downregulate expression of endothelial nitric oxide synthase (eNOS) and thus decrease nitric oxide production (Vallance et al 1997, Verma et al 2002. This effect appears to be mediated via a decrease in the stability of eNOS messenger RNA (Verma et al 2002).…”
mentioning
confidence: 99%